Adsorption thermodynamics of a lattice–gas model with non-additive lateral interactions on triangular and honeycomb lattices - Pinto, Oscar Alejandro (2010)
Adsorption thermodynamics of a lattice- gas model with non- additive interactions between adsorbed particles for triangular and honeycomb lattices is discussed in the present study. The model used here assumes that the energy which links a certain atom with any of its nearest- neighbors strongly depends on the state of occupancy in the first coordination sphere of that adatom. By means of Monte Carlo simulations in the grand canonical ensemble the adsorption isotherms and isothermal susceptibility (or equivalently the mean square density fluctuations of adparticles) were calculated and their striking behavior was analyzed and discussed in terms of the low temperature phases formed in the system.